Pengaruh Dimensi EVP dan Ethical Leadership terhadap Employee Loyalty melalui Job Satisfaction pada Guru Sekolah Swasta - Christie, Octavani; Tanuwijaya, Justine; Nilasari, B Medina (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine the effects of Career Development, Work Environment, and Ethical Leadership on Employee Loyalty, with Job Satisfaction as a mediating variable among private school teachers. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 127 private school teachers and analyzed using Structural Equation Modeling (SEM) with AMOS. The validity and reliability tests indicated that all constructs met the required criteria, except for one indicator of the Work Environment variable, which was excluded from the model. The results show that Career Development and Ethical Leadership have a positive and significant effect on Job Satisfaction, while Work Environment does not significantly affect Job Satisfaction. Furthermore, Work Environment and Job Satisfaction have a positive and significant effect on Employee Loyalty, whereas Career Development and Ethical Leadership do not have a direct effect on Employee Loyalty. Job Satisfaction is proven to mediate the effects of Career Development and Ethical Leadership on Employee Loyalty, but it does not mediate the effect of Work Environment on Employee Loyalty. In conclusion, Job Satisfaction plays a critical role in strengthening teacher loyalty and linking Employee Value Proposition dimensions to Employee Loyalty.